2017
DOI: 10.1002/app.44787
|View full text |Cite
|
Sign up to set email alerts
|

Alginate‐gelatin blend with embedded voids for controlled release applications

Abstract: Alginate gel is known for its potential use in the controlled release of drugs, and as a 3-D structure for tissue harvesting. In this paper, the tuning of the performance of alginate gel by blending gelatin in the aqueous phase, and introducing bubbles in a regular alignment are discussed. Monodisperse bubbles in millimetre or submillimeter size were introduced into the aqueous suspension of the blend prior to gelation, using a novel fluidic arrangement. The CaCl 2 solution, added as the crosslinker diffused i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The stress response was nonlinear due to the expulsion of aqueous fluid from the pore space of the hydrogel composite. Our experience suggests that upon release of the stress, the structure imbibes the previously expelled fluid, and swells to the original shape, as long as the deformation is small . Further, this was noticed that for the same level of deformation, the stress was much higher in case of the film with no voids.…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…The stress response was nonlinear due to the expulsion of aqueous fluid from the pore space of the hydrogel composite. Our experience suggests that upon release of the stress, the structure imbibes the previously expelled fluid, and swells to the original shape, as long as the deformation is small . Further, this was noticed that for the same level of deformation, the stress was much higher in case of the film with no voids.…”
Section: Resultsmentioning
confidence: 70%
“…The ultimate stress at which the adhesion broke is 12.9 kPa. This value is on similar order as the tensile strength of wet alginate film, and as such, cohesive failure in alginate layer prior to break in adhesion at the interface cannot be totally ruled out for such soft structure. For the composite film in this study, the detachment of the two layers at the interface was confirmed from visual observations.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The gas phase was injected using a mass flow controller (Alicat Scientific, U.S.A). The liquid and the gas flow rates were precisely maintained at 8 mL/min and 1 mL/min respectively 18,29,33 . The stretching and squeezing of the gas string at the tip of the fluidic device resulted in breaking of gas string into small and uniform bubbles.…”
Section: Methodsmentioning
confidence: 99%
“…The performance of a hydrogel can be improved by inserting voids in the gel matrix at the time of fabrication 18,19 . There are different methods to embed voids within polymer matrix, such as emulsion freeze drying, solvent casting or particulate leaching, fibre bonding, thermal phase separation, electrospinning, gas foaming, and through use of supercritical CO 2 20 .…”
Section: Introductionmentioning
confidence: 99%